Correlation between pathological tumour stage and lymph node involvement in oral cancers: a descriptive study - Paul, Deepak; Babu, Moothedathparambil Ramakrishnan; Marar, Krishnakumar (International Surgery Journal, 2018)
Background: Involvement of cervical lymph nodes is the single most important prognostic factor in oral carcinoma. This study was aimed to evaluate the correlation between tumour stage and lymph node metastasis. Methods: A descriptive study was planned in oral cancer patients who fall within the inclusion criteria. This was compared with the postoperative histopathologic status of cervical nodes. Correlation analysis was done between tumor stage and lymph node metastasis. Results: Total 106 patients were included in the study. The male female ratio was 1.4:1. Majority of the patients 37(34.9%) were in the sixth decade of life. Carcinoma of the tongue was present in 17 cases while only 4 had carcinoma of lower alveolus. Most of the patients with oral cancer presented at an early stage (T1-T2). Stage IV was the commonest with 51 (48.1%) patients. Level I was the most commonly involved lymph node station (78.1%) in squamous cell carcinoma of oral cavity. A weak significant positive correlation between tumor stage and lymph node metastases (r =0.298) was found (p = 0.002). There was a moderate significant (p = 0.0001) positive correlation (r = 0.435) between pathological tumour stage and level of lymph node involvement. But the positive correlation was not statistically significant in carcinoma of the lower alveolus (r = 0.387, p=0.112). Conclusions: Significant positive correlation between pathological tumor stage and level of lymph node involvement in oral cancer and carcinoma tongue. But, in carcinoma lower alveolus the positive correlation was not significant.